HIP HOP MUSIC OF SIANTAR RAP FOUNDATION AT PEMATANGSIANTAR, NORTH SUMATERA - Sinaga, Dea; Amir Razak; I Nyoman Cau Arsana (Institut Seni Indonesia (ISI) Surakarta, 2025)
This research examines how Siantar Rap Foundation (SRF) integrates traditional Batak musical elements into the modern hip hop genre through creative musical practices. SRF does not merely adopt hip hop as a global trend, but also fuses it with Batak identity and values through the selection of instruments, musical arrangement, the use of Batak-language lyrics, and the strengthening of visual identity in every performance. Using a qualitative method and an ethnomusicological approach, this research explores the mechanisms of cultural integration in SRF’s works and their impact on the cultural identity of Batak youth. The findings reveal that SRF has successfully created a phenomenon of musical hybridity that is relevant to contemporary developments and capable of reaching national and even global audiences. Through strategies such as consistent music production, live performances in various cities, digital media utilization, and the reinforcement of Batak visual culture, SRF demonstrates that hip hop music can serve as a dialogic space between local and global cultures. This study is expected to enrich the discourse on music, culture, and identity, as well as inspire other musicians to explore local culture through global music genres.